Phage and Nucleocytoplasmic Large Viral Sequences Dominate Coral Viromes from the Arabian Gulf - Mahmoud, Huda; Jose, Liny (Frontiers in Microbiology, 2017)
Corals that naturally thrive under extreme conditions are gaining increasing attention due to their importance as living models to understand the impact of global warming on world corals. Here, we present the first metagenomic study of viral communities in corals thriving in a thermally variable water body in which the temperature fluctuates between 11 and 39°C in different seasons. The viral assemblages of two of the most abundant massive (Porites harrisoni) and branching (Acropora downingi) corals in offshore and inshore reef systems in the northern Arabian Gulf were investigated. Samples were collected from five reef systems during summer, autumn and winter of 2011/2012. The two coral viromes contain 12 viral families, including ten dsDNA viral families [Siphoviridae, Podoviridae, Myoviridae, Phycodnaviridae, Baculoviridae, Herpesviridae, Adenoviridae, Alloherpesviridae, Mimiviridae and one unclassified family], one-ssDNA viral family (Microviridae) and one RNA viral family (Retroviridae). Overall, sequences significantly similar to Podoviridae were the most abundant in the P. harrisoni and A. downingi viromes. Various morphological types of virus-like particles (VLPs) were confirmed in the healthy coral tissue by transmission electron microscopy (TEM), including large tailless VLPs and electron-dense core VLPs. Tailed bacteriophages were isolated from coral tissue using a plaque assay. Higher functional gene diversity was recorded in A. downingi than in P. harrisoni, and comparative metagenomics revealed that the Gulf viral assemblages are functionally distinct from Pacific Ocean coral viral communities.